GREEN SUPPLY CHAIN MANAGEMENT AS ANTECEDENT OF GREEN SATISFACTION: EXAMINING SEQUENTIAL MEDIATION OF GREEN MARKETING AND GREEN CORPORATE IMAGE - Ploenhad, Jatturong; Khasasin, Rungarun; Khasasin, Kairung; Prachuabmoh, Arjaree (International Journal of Supply Chain Management, 2020)
The main objective of this study is to examine the impact of green supply chain management, green marketing, and image on the Green satisfaction of dairy industry of Indonesia. Furthermore, the sequential mediation of green marketing and image is examined in the present study as well. Data is collected from 550 the customers of dairy products through surveys. The response rate of data collection was 57%. In order to test the hypothesis and analysis of the data, in this study for data analysis we have adopted the Partial Least Squares Structural Equation Modelling (PLS-SEM) approach. All of the proposed hypothesis of the present study has proved to be significant showing that image, green marketing and green supply chain management practices of organization are important for the industry to gain the Green satisfaction because customers are more environmental conscious. The findings of the study are important for the policy makers of dairy milk sectors to derive the policies to satisfy the customers. Moreover, the present study also fills the gap of limited studies regarding the Green satisfaction in supply chain context.